Properties of high strength palm oil clinker lightweight aggregate concrete containing palm oil fuel ash as partial cement replacement with inclusion of 1% sika visco-crete®-2199 - Nur Azzimah, Zamri (2021)
In Malaysia, the abundance of palm oil wastes namely palm oil clinker (POC) and palm oil fuel ash (POFA) continuously increasing due to high palm oil demand. These two types of waste are usually dumped at the nearby landfill which causes environmental problems. It is observed that the utilization of palm oil fuel ash in palm oil clinker lightweight aggregate concrete has yet to be explored. Thus, it is seen that the use of these two types of palm oil waste materials in high strength concrete production would reduce some of the total amount of waste disposed at landfill. Furthermore, POC used as coarse aggregate in high strength concrete would preserve natural resources such as granite and limestone for future generation. Thus, this research was conducted to investigate the mechanical, durability and elevated temperature performances of high strength palm oil clinker lightweight aggregate concrete containing palm oil fuel ash as partial cement replacement with 1% SIKA Visco-Crete®-2199. Trial mixes were conducted to select the best high strength concrete mix by taking into account the density, workability and strength. After the best mixes was determined, five types of POC mixes of Grade 60 were prepared consisting of 0%, 10%, 20%, 30% and 40% POFA as partial cement replacement with 1% SIKA Visco-Crete®-2199. In this research, high strength POC lightweight aggregate concrete with 100% OPC and incorporation of 1% SIKA Visco-Crete®-2199 (OPC LWAC) act as control specimen and 3500 specimens comprising of cubes, prisms and cylinders were prepared and tested throughout this experimental study. At the first stage, the effect of POFA content as partial cement replacement towards compressive strength of high strength POC lightweight aggregate concrete with 1% SIKA Visco-Crete®-2199 were investigated. Then, the effect of curing methods towards mechanical, durability and elevated temperature were investigated. Four types of curing methods namely water curing, air curing, initial water curing and plastic curing were used to examine the mechanical properties of POC LWAC containing POFA as partial cement replacement with 1% SIKA Visco-Crete®-2199 in terms of compressive strength, flexural strength, splitting tensile strength and modulus of elasticity. These four curing regimes were also used to determine their affect towards durability aspects namely acid attack, sulphate resistance, carbonation and water absorption. Apart from that, elevated temperature test was conducted and the specimens were cooled using air cooling. From the results, they show that 10% POFA replacement resulted in better performance than other POFA replacements when subjected to all types of curing. The findings also show that water curing is the best curing method for mechanical and durability testing. On the other hand, air curing is not suitable as it disturbs the reactions needed for production of calcium silicate hydrate gel causing lower amount of the gel and strength. Water curing promotes better hydration process and pozzolanic reaction that improves the internal structure of POC LWAC containing POFA with 1% SIKA Visco-Crete®-2199 causing it to exhibit lower absorption rate as compared to other curing. High strength concrete specimens containing 10% POFA also exhibit better resistance upon subjected to elevated temperature.